Subjective meanings and expressions of marital love among soon-to-be-married urban Malays - Mohd Hoesni, Suzana; Mohd Hashim, Intan Hashimah; Chong, Sheau Tsuey; Mohamad, Mohd Suhaimi; Jusoff, Kamaruzaman; Subhi, Nasrudin; Sarnon @ Kusenin, Norulhuda; Nen, Salina; Mohamad, Lukman @ Zawawi (IDOSI Publications, 2011)
Studies have shown that many married couples experience "deterioration of love" after marriage. A positive perception on love is crucial in ensuring a happy and satisfied marriage. Unhappy marriages are related to many psychological and developmental problems to the individual and individuals around the married couples. Thus, the aim of this study is to explore how soon-to-be married urban Malays give meanings and express marital love. Implicit approach to studying love was applied using the prototype love theory. Participants of the study were 245 soon-to-be-married urban Malays attending a compulsory premarital course within Federal Territory, Malaysia. Questionnaires consisted of participants' personal background information, information on relationships and questions on how participants' give meanings and express marital love. Findings indicated that participants give meanings to marital love by relating to gain God's blessings. Findings also showed that "where" and "who" was present during the expressions of marital love were important in determining the kind of expressions of marital love among urban Malays. Results also showed that expressions of marital love which involve physical contact were less desirable. Implications and future direction of this research were also discussed.